2011
DOI: 10.1016/j.jsbmb.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Human adrenal cells that express both 3β-hydroxysteroid dehydrogenase type 2 (HSD3B2) and cytochrome b5 (CYB5A) contribute to adrenal androstenedione production

Abstract: Androstenedione is one of several weak androgens produced in the human adrenal gland. 3β-hydroxysteroid dehydrogenase type 2 (HSD3B2) and cytochrome b5 (CYB5A) are both required for androstenedione production. However, previous studies demonstrated the expression of HSD3B2 within the zona glomerulosa (ZG) and fasciculata (ZF) but low levels in the zona reticularis. In contrast, CYB5A expression increases in the zona reticularis (ZR) in human adrenal glands. Although their colocalization has been reported in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…with little alterations in the adjacent ZG and ZF [13]. Results of our recent study also revealed for the first time the presence of adrenocortical parenchymal cells located between the ZF and ZR co-expressing both CYB5A and 3βHSD [12]. Therefore, it is also reasonably postulated that these cells are positive for CYP17 since they are located in the border between ZF and ZR.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…with little alterations in the adjacent ZG and ZF [13]. Results of our recent study also revealed for the first time the presence of adrenocortical parenchymal cells located between the ZF and ZR co-expressing both CYB5A and 3βHSD [12]. Therefore, it is also reasonably postulated that these cells are positive for CYP17 since they are located in the border between ZF and ZR.…”
Section: Introductionmentioning
confidence: 70%
“…3β-hydroxysteroid dehydrogenase (3βHSD) is considered a key enzyme converting DHEA to androstenedione [411]. Results of previous in vitro studies all demonstrated that an inhibition of both 3βHSD and CYB5A resulted in marked repression of androstenedione production, suggesting that efficient androstenedione production may require the presence of both enzymes in the one cell [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, 3␤HSD is expressed in the zona fasciculate (ZF) and zona glomerulosa (ZG) in the absence of significant Cyt-b 5 expression [42,43]. Nakamura et al [44] recently highlighted the importance of Cyt-b 5 and 3␤HSD coexpression in the production of A4 and identified a layer of adrenocortical cells located at the border between the ZF and ZR that coexpress both 3␤HSD and Cyt-b 5 in the presence of CYP17A1. Until now, Cyt-b 5 was only thought to play a role in the stimulation of the 17, 20-lyase reaction catalyzed by CY17A1, however, based on the results presented in this paper we suggest that Cyt-b 5 may also stimulate 3␤HSD activity, thereby promoting the formation of A4 from DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of increased androgen production as a result of decreased HSD3B2 activity was also demonstrated by McCartin et al when they reported the presence of premature adrenarche in an 11-year-old subject with a profound loss in HSD3B2 activity owing to a compound heterozygotic mutation in the HSD3B2 gene (44). However, it should be noted that there are cortical cells located at the border between ZF and ZR in normal adult adrenal glands that co-express HSD3B2 and CYB5, suggesting that these cells have the potential for direct production of androstenedione (45). Human ovarian theca cells also co-express HSD3B2, CYP17 and CYB5 and similarly have potential for androstenedione biosynthesis (29, 46).…”
Section: Steroidogenic Enzymes and Cofactors Involved In C19 Steromentioning
confidence: 99%